UPAYA MENINGKATKAN HASIL BELAJAR IPA MELALUI METODE PEMBELAJARAN ACTIVE LEARNING TIPE QUIZ TEAM PADA SISWA KELAS V SDN 12 SUNGAI LIMAU - Yuelmi, Yuelmi (STKIP Pesisir Selatan, 2019)
The success of learning objectives is determined by many factors including the teacher's factor in carrying out the teaching and learning process, because the teacher can directly influence, foster and improve students' intelligence and skills. To overcome the above problems and to achieve maximum educational goals, the role of the teacher is very important and it is expected that the teacher has a good teaching method and is able to choose the right learning method and in accordance with the concepts of the subjects to be delivered. The problems to be examined in this study are: Is using the Learning Method Active Learning Type Quiz Team able to improve the science learning outcomes of Class V students at SDN 12 Sungai Limau? The purpose of this action research is to improve the learning outcomes of science through the use of the Active Learning Type Quiz Team Learning Method for students VI.C SDN 12 Sungai Limau. This study used classroom action research as much as two rounds. Each round consists of four stages, namely: planning, implementation, observation, reflection. The target of this study was the fifth grade students of SDN 12 Sungai Limau. The data obtained are quantitative and qualitative data. From the results of the analysis it can be seen that the students' understanding of the material presented by the teacher is more stable (learning completeness increases from cycle I, and II, ie 61.76%, and 88.24% respectively). students have achieved classically. The conclusion of this study is that the Learning Method of Active Learning Type Quiz Team has a positive influence, which can improve student learning outcomes as indicated by the average student answer stating that students are interested and interested in the Active Learning Type Quiz Learning Method Team so that they become motivated to learn